A climatic study with special reference to delayed foliation of deciduous fruit trees - De Villiers, G. D. B.(Gabriel Daniel Bosman) (Stellenbosch : Stellenbosch University, 2012)
Thesis (D. Sc.) -- University of Stellenbosch, 1938.